Analysis of the Potential of New Post - Abolition Election Systems and Regulations Presidential Threshold - A. Wicakksono, Haryo; Pribadi Uang, Dedi; Hasibuan, M. Sukron; S. K. Milala, Enda; A. Kamdani, Juan; C. W, Rothreya (Fakultas Ilmu Sosial UIN Sumatera Utara Medan, 2025)
This study aims to analyze the system of changes to the election and its impact after the abolition of the parliamentary threshold (PT) in Indonesia in accordance with Law No. 7 of 2017. The research approach used is descriptive qualitative, namely observing the general election process carried out using data analysis by Miles and Huberman. The results of the study indicate that the abolition of the parliamentary threshold provides an opportunity for political parties with small votes to nominate presidential candidates or candidates for members of the regional representative council. However, there is an impact caused by the abolition of this PT where the opportunity to become a presidential candidate is numerous opportunities so that people through political parties can nominate themselves. Thus necessitating a second round. The implementation of the second round has an impact on the implementation of the election policy, especially in terms of increasing the budget which significantly drains the state budget which should only be one round. This problem not only impacts the state budget but also influences the emergence of divisions among the community due to political differences